INTERLINGUAL AND INTRALINGUAL ERRORS IN WRITING NARRATIVE TEXT MADE BY JUNIOR HIGH SCHOOL AND SENIOR HIGH SCHOOL STUDENTS - Pratiwi, Andini Puji (Jurnal Penelitian Humaniora, 2015)
The present study investigates the interference of L1 (Indonesian) into L2 (English) and the errors that occur due to the influence of TL (target language). The focus of the study is on the errors committed by these EFL learners in writing narrative text and emphasized on interlingual and intralingual errors. The objectives of the study are to investigate the errors committed by these EFL learners in order to find out; (1) the types of interlingual and intralingual errors in Junior High School and Senior High School, (2) frequencies of interlingual and intralingual errors in Junior High School and Senior High School, and (3) similarities and differences of interlingual and intralingual errors in Junior High School and Senior High School. To achieve these objectives, writing test was utilized in this study. The subjects of the study comprisedÂ 35 of ninth graders and 35 tenth graders in Pekanbaru, Riau. The findings of the study suggest: (1) The types of interlingual and intralingual errors made by JuniorÂ High school and Senior High School divided into 2 levels, they are morphological level and syntactical level; (2) the frequency of interlingual errors in Junior High School 27,82% and 14,04% in Senior High School. The frequency of intralingual errors in Junior High School 72,17% and 85,96% in Senior High School; and (3) The similarities of interlingual and intralingual errors found in Junior High School and Senior High School are 2 types in morphological level and 2 types in syntactical level. The differences of interlingual and intralingual errors found in Junior High School and Senior High School are 1 type in morphological level and 11 types in syntactical level.